Plan de marketing para la asociación Cofradía Huacupamba de la ciudad de Amaluza, cantón Espíndola, provincia de Loja, para el año 2017 - Salazar Jiménez, Diana Abigail (2017)
This research was carried out with the purpose of providing a Marketing Plan for the Huacupamba Cofradía Association, of the city of Amaluza, Cantón Espíndola, Province of Loja for the year 2017, in which strategic objectives were established that will allow to position the Association as one of the best in the market. For the accomplishment of the present work the deductive, scientific, statistical, historical methods were used; As well as the techniques of interview, survey and direct observation for the collection of data and information. An interview was conducted with the president of the association, 47 partners were interviewed and a sample of 374 inhabitants of the Espndola canton. The results were initiated by performing a situational diagnosis where the external factors of the association were analyzed; Socio-cultural, economic, political and technological factors, as well as the five forces of Porter, and then established the matrix of External Factors Evaluation (EFE), whose weighted result was 3.01, indicating that the association takes advantage of opportunities and Minimizes the existing threats, as well as proceeded to perform the analysis of internal factors of the "Huacupamba Guild Association" through the matrix of Internal Factor Assessment (EFI) gave a weighted result 2.9, which means that Leverages the strengths to minimize weaknesses. Once the SWOT Matrix was established, which determines the most relevant strengths, opportunities, weaknesses and threats that the association possesses, a high impact matrix was established, which allowed four strategic objectives to be established: "Empowering partners with "Creating advertising through the most popular media in the Canton," "Making agreements with organizations to support economic development projects," " Mark that allows to differentiate the products and services offered by the Association of others existing in the market ", which in their structure are constituted as follows; Strategies, goals, activities, time, managers and budget. With the establishment of the strategic objectives, it was possible to carry out the proposal of the Marketing Plan for the association, which presented the necessary budget to put into practice the one that has a value of $ 2785.00 dollars. At the end of the work are the conclusions and through them the respective recommendations that are presented for the association.